The influence of shoulder pain on functional limitation, perceived health, and depressive mood in patients with traumatic paraplegia. (September 2015) - Wang, Jia-Chi; Chan, Rai-Chi; Tsai, Yun-An; Huang, Wen-Cheng; Cheng, Henrich; Wu, Han-Lin; Huang, Shih-Fong
Abstract : Objective: To assess whether functional activity, perceived health, and depressive symptoms differ between individuals with traumatic paraplegia with and without shoulder pain. Design: Cross sectional and comparative investigation using the unified questionnaire. Setting: Neural Regeneration and Repair Division unit of Taipei Veterans General Hospital in Taiwan. Participants: Seventy-six patients with paraplegia (23 with and 53 without shoulder pain) who had experienced spinal cord injury at American Spinal Injury Association Impairment Scale T2 to T12 neurologic level (at least 6 months previously). Outcome measures: Spinal Cord Independence Measure (SCIM), a single item from the Medical Outcomes Study 36-Item Short-Form Health Survey, and Patient Health Questionnaire-9 (PHQ-9) depression scale. Results: Shoulder pain was prevalent in 30% patients. Patients with shoulder pain had significantly worse perceived health and greater depressive symptoms than those without. No significant difference was found in functional ability between groups. Greater shoulder pain intensity was related to higher depressive scores ( r = 0.278, P = 0.017) and lower self-perceived health scores ( r = −0.433, P < 0.001) but not SCIM scores (P = 0.342). Conclusion: Although shoulder pain was unrelated to functional limitation, it was associated with lower perceived health and higher depressive mood levels.